JOURNAL OF PHYSICAL EDUCATION COURSE FROM UNIOESTE: ANALYSIS OF SCIENTIFIC PRODUCTION FROM 1999 TO 2010 - Robson Frank; Angela Schone; Anne Caroline Duarte; Jalusa Andréia Storch; Willian Cavalli; Douglas Roberto Borella (Universidade Estadual do Oeste do Paraná, 2013)
The scientific production is critical to the dissemination of new knowledge, to push science, technology and innovation in different areas of knowledge, and is considered complete when its results are published by means of journals or other sources. We analyzed the Caderno de Educao Fsica Estudos e Reflexes, linked to the Physical Education course at the Universidade Estadual do Oeste do Paran UNIOESTE in period 1999 to 2010, seeking to know the characteristics and peculiarities of the publications of this journal. The study analyzed 143 articles over the 15 editions of the journal. The results showed a trend of research linked to school and health and quality of life. However, it may be noted, in general, their studies had been conducted by small groups of people who publish many articles, and, in a way, limiting for the development of the journal, providing little interdisciplinary exchange of knowledge. In the course of its 11 publication year (1999 - 2010), there were increases in various aspects of the journal, regularity such as the issue of its scientific production from the year 2008, which are currently available in semiannual editions in print and online, in addition to the more rigorous in reviews of articles accepted by the body editorial, for being a positive increase in their national prestige. With the evaluation of some factors will can further leverage the prestige of the journal, and looks upon new approaches involving humans and education movement in their different fields of knowledge.